Pengaruh Pemberian Steroid Topikal Terhadap Tekanan Intra Okular : Sebuah Tinjauan Pustaka - Lauw, Jessica Amelia; Muthia, Annisa Sri Rachma; Pangaribuan, Beatric Ruth Fransiska; Anugrahsari, Santi (Universitas Kristen Krida Wacana, 2024)
The use of topical corticosteroids, especially in the periocular area, has been associated with increased intraocular pressure (IOP), potentially leading to glaucoma and other eye complications. This study evaluated the risk of IOP elevation due to topical corticosteroid use and its influencing factors. This study is a literature review investigating the relationship between topical corticosteroid use and IOP elevation. Data were collected from studies reporting the effect of topical corticosteroids on IOP, including the type of steroid, duration of use, frequency of administration, and patient age. The findings suggest that the use of topical corticosteroids can lead to a significant increase in IOP, with the risk varying depending on the type of steroid, duration, and frequency of use, as well as individual patient characteristics such as age. Although some studies showed a significant increase in risk, other results showed minimal risk, suggesting the need for close monitoring of IOP in patients using topical corticosteroids. The use of topical corticosteroids in the periocular area requires careful consideration of the potential risk of increased IOP. It is important to choose steroids with low anti-inflammatory potential and monitor IOP regularly to reduce the risk of IOP-related side effects. Further studies are needed to fully understand the risks associated with using periocular topical corticosteroids and develop guidelines for safe use.